Single doses of diphtheria-tetanus-pertussis and poliomyelitis vaccines are sufficient to generate a booster-type response to tetanus in most migrant children. Issue 43 (8th October 2019) - Fougère, Yves; El Houss, Samir; Suris, Joan-Carles; Rouvenaz-Defago, Sylvie; Miletto, Damien; Von der Weid, Lucie; Willen, Fanny; Williams-Smith, Joanne Anesta; Gehri, Mario; Crisinel, Pierre Alex
Abstract: Background: Immunization coverage for three doses of the diphtheria-tetanus-pertussis and poliomyelitis vaccines in infants is high worldwide, therefore despite the lack of documentation of past vaccinations, most migrant children do not require complete revaccination. Our strategy was to administer a single dose of a tetanus toxoid containing vaccine (TTCV) to migrant children followed by anti-tetanus toxoid (TT) serology to determine whether additional vaccine doses were required. Our goal was to estimate the basic TTCV coverage and to identify potential determinants of the vaccination response. Methods: Newly arrived migrant children were prospectively enrolled between October 2014 and August 2017. We included patients aged 1–18 years with no proof of past vaccinations who accepted a single dose of TTCV. Anti-TT serology was performed after 4–6 weeks, and an anti-TT level ≥ 1 IU/mL was considered a booster-type antibody response with no need for additional doses of TTCV. Potential determinants of the vaccination response were identified using univariate and multivariate linear regression analyses. Results: Two hundred and eight children were eligible for analysis. The mean age of the children was 9 (±4.5) years and 100 (48%) were female. The majority (n = 129, 62%) of the children came from the WHO Eastern Mediterranean region. Only three patients (1.4%) required additional vaccine doses. A Syrian origin (p < 0.001) and direct arrival primarily by airplane into Switzerland without transiting through other European countries (p = 0.029) associated with higher anti-TT levels in a multivariate regression model (multiple r2 = 0.210, p < 0.001). Conclusion: A single dose of TTCV is enough to generate long-term protection in most migrant children. In the context of high basic vaccination coverage, the strategy, which consists of administration of a single dose of TTCV followed by anti-TT serology, can be considered where serotesting is available and economical.